Implementasi Model Diskusi Kelompok Sebagai Strategi Penguatan Kerja Sama Siswa pada Pembelajaran Teks Prosedur Bahasa Indonesia di Kelas IV SDN 8 Selat Penuguan - Siti Marhamah (Katalis Pendidikan : Jurnal Ilmu Pendidikan dan Matematika, 2026)
This study aims to describe the implementation of the group discussion model as a strategy to strengthen students' collaboration in Indonesian procedural text learning in Grade IV of SDN 8 Selat Penuguan. The study focuses on the implementation of group discussion, the forms of students' collaboration, the teacher's role in guiding collaboration, and the supporting and inhibiting factors in the learning process. This research employed a descriptive qualitative approach. The primary data were obtained from the teacher and Grade IV students, while supporting data were collected from learning documents. Data were gathered through observation, interviews, and documentation, and were analyzed through data reduction, data display, and conclusion drawing. Data validity was strengthened through source and technique triangulation. The findings indicate that group discussion was implemented through planning, small-group formation, procedural-text-based tasks, discussion, presentation, feedback, and reflection. The model strengthened students' collaboration through task sharing, mutual assistance, expressing opinions, listening to peers, and taking responsibility for group outcomes. The teacher acted as a learning designer, facilitator, guide, communication mediator, and evaluator of collaborative processes. Supporting factors included teacher readiness, the suitability of procedural text material, the use of worksheets, and a conducive classroom climate, while inhibiting factors included uneven student participation, limited time, differences in language competence, and the dominance of particular students in group work. The study concludes that the group discussion model is relevant for procedural text learning because it integrates material comprehension with the development of elementary students' social skills.